Concepção de um modelo de distribuição de gás natural liquefeito para o Estado do Ceará - Freitas Filho, Manoel Messias de (2008)
This work presents an alternative approach to the Brazilian natural gas market development, particularly to the State of Ceará, suggesting a liquefied natural gas (LNG) distribution model to the regions that are not supplied by gas pipeline, in an efficient way to complement the existing distribution system. In a such way, we researched to know the LNG chain, its evolution in the world-wide market and the support infrastructure to the transport and distribution. Using these information, we intended to plan the liquefied natural gas infrastructure distribution model (LNGDM) considering the logistic and operational research frameworks. In the model conception, the infrastructure considered to the LNG distribution formulation were: the Pecém Port LNG terminal, the existing highway-rail system in the State of Ceará and the infrastructure concepts to the LNG distribution in the Ceará State sub-areas. The model suggests a new layout for the LNG distribution chain in the State, allows to a technical and economic evaluation of the optimized used infrastructures that compose the model, showing the most efficient form, with the minimum cost, and promotes the accessibility of the natural gas to the regions not supplied by gas pipelines.